Feasibility of breast conserving surgery in multifocal breast cancers - Kadioglu, HÜSEYİN; KADIOĞLU, HÜSEYİN; YUCEL, Serap; Yildiz, Seyma; YILDIZ, ŞEYMA; Bozkurt, SÜLEYMAN; BOZKURT, SÜLEYMAN; Ersoy, YELİZ EMİNE; ERSOY, YELIZ EMINE; SAGLAM, Esra; MUSLUMANOGLU, Mahmut (My University, 2014)
BACKGROUND: Multifocal breast cancers (MFBCs) present a challenge to surgeons. Although its feasibility is still controversial, breast-conserving surgery (BCS) is not contraindicated for MFBCs. The investigators retrospectively evaluated the feasibility of BCS and reviewed histopathologic findings in patients with MFBC.